How COVID-19 Has Changed Crowdfunding: Evidence From GoFundMe - Wang, Junda; Luo, Jiebo; Zhang, Xupin (Frontiers in Computer Science, 2022)
While the long-term effects of the COVID-19 pandemic have yet to be determined, its immediate impact on crowdfunding is nonetheless significant. This study adopts a computational approach to better understanding this consequence. We aim to gain insight into whether and how the COVID-19 pandemic has changed crowdfunding. Using a unique dataset of all GoFundMe campaigns published over the past two years, we explore the factors that have led to successfully funded crowdfunding projects. In particular, we study a corpus of 36,370 projects from Nov 2018 to Dec 2020 by analyzing cover images and other attributes commonly found on crowdfunding sites. We first construct a classifier and a regression model to assess the importance of features based on XGBoost. Next, we employ counterfactual analysis to investigate the causality between features and the success of crowdfunding. Furthermore, sentiment analysis and paired sample t-tests are performed to examine differences in crowdfunding campaigns before and after the COVID-19 outbreak in March 2020. Findings suggest a significant racial disparity in crowdfunding success. In addition, sad emotions expressed in a campaign’s description became significant after the COVID-19 outbreak. This study enriches our understanding of the impact of the COVID-19 pandemic on crowdfunding as well as the prevalence of discrimination in crowdfunding.